PENGUATAN PROFESIONALISME CALON GURU PPKN MELALUI MODEL SIMULASI MENGAJAR BERBASIS 4C: Penguatan Profesionalisme Calon Guru PPKn melalui Model Simulasi Mengajar Berbasis 4C (Critical, Creative, Collaborative, Communicative) - Wikan Sasmita; Hamidah Ulfa Fauziah; Etty Andyastuti; Agus Widodo; Nursalim; Suratman (Wisesa: Jurnal Pengabdian Masyarakat, 2025)
This community service program aims to strengthen the professionalism of prospective Pancasila and Citizenship Education (PPKn) teacher students through the implementation of a 4C-based teaching simulation model (critical thinking, creativity, collaboration, and communication). The background of the activity is based on the need to strengthen 21st-century teacher competencies that require mastery of critical thinking skills, learning creativity, professional collaboration, and effective communication as an integral part of teacher professionalism. The implementation method uses a participatory training approach structured in four stages, namely pre-implementation (need assessment and professionalism pre-test), core implementation (4C concept strengthening workshop and preparation of learning tools), teaching simulation practice (10–15 minutes of microteaching per participant accompanied by observations using the 4C rubric), and reflection and evaluation (peer feedback, self-reflection, and professionalism post-test). Program evaluation is carried out through a comparison of pre-test and post-test scores, supported by microteaching observation data and participant reflections to describe changes in professionalism quantitatively and qualitatively. The expected outcomes of this activity are an increase in the professional attitudes of prospective PPKn teachers, the ability to design and implement innovative learning, and strengthening the 4C competencies reflected in the quality of communication, creative learning strategies, collaboration with colleagues, and critical thinking skills in pedagogical decision-making. This program also produces outputs in the form of 4C-based learning tools, a teaching simulation assessment rubric, and recommendations for implementing models for developing microteaching learning in study programs.